A Micro-Level Assessment Methodology for Attaining Programme Outcomes through Under Graduate Engineering Projects - Karthikeyan, P.; Abirami, A. M.; Thangavel, M. (Journal of Engineering Education Transformations, 2021)
The Programme Outcomes (PO) of students are measured after the completion of every Under Graduate (UG) programme. Contributions of engineering projects on programme outcomes are significantly more when compared with other courses. The final year projects are evaluated by rubrics at different stages. The projects may fall in different categories; mapping of each project with PO needs to be carried out based on the nature of the problem and its solution. Hence, there exists a need for micro-level assessment and evaluation processes for projects. It is really a challenging process to define the set of activities needed for this. In this paper, a micro-level assessment methodology for attaining programme outcomes through UG Engineering Projects has been proposed and implemented. The process is defined in alignment with the ADDIE instructional design model and recommended to have different phases like plan, design, implement, evaluate and assessment. Project-PO mapping guidelines are prepared and used in the assessment process. This study explores the attainment level of different POs for each student and analyzes how the project helps in the attainment of Graduate Attribute (GA) for each individual. This paper discusses the detailed processes that have been carried out for the project course and how these processes help in the PO attainment level for two different batches of BTech IT students. The results of PO attainment prove that the proposed process would help in the attainment of PO, hence the Graduate Attribute level of each student.